Synthesis and characterization of novel efficient and thermally stable 2-aryl-5-dicyanovinylthiophenes and 5-aryl-5´-dicyanovinyl-2,2´-bithiophenes as potentially promising nonlinear optical (NLO) materials - Herbivo, Cyril (2010)
Two series of dicyanovinyl-substituted compounds namely 2-aryl-5-dicyanovinyl-thiophenes 4 and 5-aryl-5´-dicyanovinyl-2,2´-bithiophenes 6 were synthesized through Knoevenagel condensation of the corresponding 2-aryl-5-formyl-thiophenes 3 and 5-aryl-5´-formyl-2,2´-bithiophene 5 precursors. On the other hand, precursors 3 were prepared through the Vilsmeier-Haack-Arnold reaction (VHA) starting from inexpensive and easily available precursors such as acetophenones. This method produced the title compounds in higher yields than the recently reported synthesis via Suzuki coupling of functionalized aryl boronic acids with 5-bromo-2-formyl-thiophene. Electrochemical studies and characterization of the optical (linear and nonlinear), and thermal properties for compounds 5-6 indicate that, good nonlinearity is complemented by exceptional thermal stability for chromophores 6, making them potential candidates for several optoelectronic applications such as solvatochromic probes and nonlinear optical materials.